Interactions between aphids, their insect and fungal natural enemies and the host plant - Baverstock, Jason (2004)
Multitrophic and intraguild interactions influence the success of biological control. The interactions between Acyrthosiphon pisum, three natural enemies (Pandora neoaphidis, Coccinella septempunctata and Aphidius ervi) and the host plant, Vicia faba, were assessed. Volatiles released from aphid-damaged plants had a direct effect on P. neoaphidis indicating they may act as synomones. However, volatiles did not increase efficacy of the fungus suggesting it is not a bodyguard species. Transmission was greatest during plant colonisation by aphids and was not affected by plant condition. Infection by P. neoaphidis had a direct negative effect on the fitness of the aphid through reduced reproduction and early host death.